Natural alpha-radioactivity in bone, liver and blood samples from the various species - Shay, Malcolm MacGregor (Department of Physics, 2016)
In this thesis, samples from the various species are studied for alpha-radioactive content. The experimental technique used is one of thick source "total" alpha counting with "fast pair" scaling enabling separation of "Thorium" series contribution. A study of the change in count rate over a time period enables Po-210 activity to be determined. Additional alpha spectroscopic techniques are used to identify specific alpha emitting isotopes in the samples. Bone tissue alpha-activity levels are used as a basis for comparing levels between the species. Liver is studied as it shows interesting features, and blood is also studied. The method of sample preparation involves the removal of water from the samples at low temperatures and no additional chemical techniques are used. Thirty-six different species from four groups of animals were studied (herbivores, carnivores, omnivores and marine environment). Man shows very low levels of alpha-activity compared with other species of which the group "herbivores" show highest levels of alpha-activity, including large amounts of Po-210. The marine environment species show a large accumulation of Po-210 in liver.